Constructing University as an Organization - ПавлюткинИван Владимирович (Journal of Economic Sociology, 2011)
Declaring their aspiration for rationalization, transparency, and accountability universities confirm that organizational theory successfully translates and popularizes its concepts in the practical world. Universities start more often to deploy such ideas as development strategies, improvement management, management of quality, earn-out rights, and etc. Academic organizations actively copy and install organizational forms regulating their interaction with the important stakeholders. Today a lot of attempts are made to shape and improve university as an organization. Institutional patterns for imitation as products of the organizational knowledge development are getting more and more important. A question is raised whether universities remain a unique form of organization or they become similar to standard formal organization described by major perspectives in organizational theory.университет